PENGARUH PENAMBAHAN QUICKCURE CX TERHADAP UJI KUAT TEKAN BETON K-500 - Agusri, Erny; Jaya, Wahyu Pratama (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2020)
Quickcure CX is a chemical for concrete designed using the latest technological innovations, this added material can accelerate and increase the compressive strength of concrete by 5 - 10% and can reduce the moisture content in the concrete mixture by 5 - 10%. The purpose of this study was to increase and accelerate the effect of the compressive strength value of concrete produced by Quickcure CX added material on K-500 concrete.The research sample is a cube-shaped test object with a size of 15cmx15cmx15cm. There are 4 sample variations, namely: Normal Concrete, Normal Concrete + Quickcure cx 0.25%, Normal Concrete + Quickcure cx 0.45%, and Normal Concrete + Quickcure cx 0.65%, each variation consisting of 15 samples.After conducting the concrete compressive strength test, this study obtained the highest average compressive strength test results in Normal Concrete (503.2kg / cm2), Normal Concrete + Quickcure cx 0.25% (513.8kg / cm2), Normal Concrete + Quickcure 0.45% (536.4kg / cm2) and Normal Concrete + Quickcure cx 0.65% at 551.6kg / cm2 at the age of 28 days. So of the 4 variations in the value of the compressive strength test of concrete, it still increases in Normal Concrete + Quickcure cx 0.65%, and accelerating the concrete does not accelerate because the average age is 21 days with a variation of Normal Concrete + Quickcure cx 0.65% with a value of 488.8 kg / cm2 so the concrete has not reached the compressive strength that was planned.Keywords: Concrete, Quikcure CX, Compressive Strength, K-500